Investigation of fibre reinforcement toward polymer production emphasizing fused deposition modelling - Sahat, Idris Mat; Oumer, Ahmed Nurye; Ahmad, Zulkifli; Rejab, Mohd Ruzaimi Mat (2019)
3D printing is one of rapid prototyping technology to fabricate 3D structure. Fused Deposition Modeling (FDM) is a popular 3D printing methods that involve extruding layers of material like Polylactic Acid (PLA).Even though FDM has some advantages but there are several difficulties that have to be faced. When setting the printing options, several parameters have to be taken into account, such as layer height, printing temperature, buildplate temperature, diameter, print speed, travel speed, infill density and infill pattern. Selecting these parameters is often a great challenge for the user, and is generally solved by experience without considering the influence of variations in the parameters on the mechanical properties of the printed parts. This research analyzes the effect of the infill percentage on the mechanical properties of Polylactic Acid (PLA) tensile speciment and flexural speciment. In order to characterize this effect, conduct tensile test and flexural test. The rapid prototyping speciment were printed at different infill percentage (30%, 50% and 70%) and different infill pattern (Grid, triangle and line) but the rest of the printing parameters were kept constant. Two different results were analyzed for these tests, tensile properties (Ultimate Tensile Strength, Tensile Stress at break, Ductility at UTS) and flexural properties (Flexural Stress, Flexural Modulus). Results showed that highest UTS is at 70% infill percentage 34.66MPa (Line pattern), highest Tensile Stress at break is at 70% infill percentage is 12.07MPa (Grid pattern), highest Ductility at UTS is at 70% infill percentage is 5.29% (Line pattern), highest Flexural Stress is at 70% infill percentage is 56.59 MPa (Grid pattern) and highest Flexural Modulus is at 70% infill percentage is 2278.48 MPa(Grid pattern). After comparing three polynomial graph for tensile properties, it conclude that line pattern is not affected by the constant printing parameter because tensile properties value increase by increasing infill percentage but triangle pattern is affected by constant printing parameter when printing at 70% and grid pattern when printing at 50% due to decreasing tensile properties value. After comparing two polynomial graph for flexural properties, it conclude that grid pattern is not affected by the constant printing parameter because flexural properties value increase by increasing infill percentage but triangle pattern and line pattern are affected by constant printing parameter when printing at 70% due to decreasing flexural properties value.